Coherent quantum states in resonant‐mass gravitational wave detectors. Issue 1 (5th January 2023) - Frajuca, Carlos; Selbach, Lucas; da Silva, Douglas Alves; de Sales, Dinalva Aires; Ferrari, Fabricio; Magalhaes, Nadja Simao
Abstract: This work describes the importance of quantum coherent states when a resonant‐mass gravitational wave detector absorbs energy from a gravitational wave in an amount very close to the quantum limit. In this case, quantum non‐demolition measurements become essential as well. As the main result, for a coherent‐state signal, the detector behaves as if the signal was a classical one.